Решить уравнение (12-х)-(3х+4)=-х-1 15+(6х-х+2)=5х (2+х)+(18-4х)=-(6х-2) -(0,5х+0,2)=х-(1,5х+0,1) 2х+(1,5-3х)=1-(х+0,7) 8-(х+1/3)=-(2х+7 1/3)

Решить уравнение (12-х)-(3х+4)=-х-1 15+(6х-х+2)=5х (2+х)+(18-4х)=-(6х-2) -(0,5х+0,2)=х-(1,5х+0,1) 2х+(1,5-3х)=1-(х+0,7) 8-(х+1/3)=-(2х+7 1/3)
Гость
Ответ(ы) на вопрос:
Гость
 (12-х)-(3х+4)=-х-1  12-x-3x-4=-x-1 8+1=-x+x+3x 9=3x x=3 Ответ: 3 15+(6х-х+2)=5х 15+5х+2=5х 5х-5х=-17 0х=-17 нет решения. (2+х)+(18-4х)=-(6х-2) 2+х+18-4х=-6х+2 20-2=-6х+4х-х 18=-3х х=-6 Ответ: -6 -(0,5х+0,2)=х-(1,5х+0,1) -0,5x-0,2=x-1,5x-0,1 -0,5x+1,5x=-0,1+0,2 x=0,1 Ответ: 0,1 2х+(1,5-3х)=1-(х+0,7) 2x+1,5-3x=1-x-0,7 -x+x=0,3-1,5 0x=-1,2 нет решения. 8-(х+1/3)=-(2х+7 1/3) [latex]8-x-1/3=-2x-7\rac{1}{3}[/latex] [latex]x+2x=-7\frac{1}{3}-7\frac{2}{3}[/latex] 3x=-15 x=-5 Ответ: -5  
Не нашли ответ?
Ответить на вопрос
Похожие вопросы